State, Heritage, and Modern Hotels. The Beginnings of Public Hotel Policies in Perú (1916-1930) - Armas Asín, Fernando (2023)
The implementation of the first promotional measures by the Peruvian government for the hotel industry is analyzed from the perspective of the interest in natural locations and the lodging needs of the city of Lima in the early 20th century. Concrete outcomes of these measures, their characteristics, and the emergence of the first hotels considered modern are presented. This aims to contribute to a better understanding of the inception of this type of lodging in Latin American countries, the associated issues, and the conditions of their development.